Pengaruh Media Sosial Terhadap Tren Gaya Hidup Sehat Generasi Muda: Literature Review - Putri Nurhasanah; Desy Chandra Haryanti; Muhammad Sapruwan; Taufiq Rachman (LPPM Politeknik Pratama, 2026)
This study aims to understand how much influence social media has on the healthy lifestyle trends of the younger generation. By conducting a literature review, this study provides insight into healthy lifestyle trends for the younger generation in facing modern challenges and adopting a healthy lifestyle, especially in daily behaviors related to healthy lifestyles, such as exercise habits, healthy eating patterns and awareness in maintaining mental and physical health. This study reveals that healthy lifestyle trends are becoming increasingly important and popular among many young people in big cities. A healthy lifestyle has now become a new symbol for the younger generation. This younger generation prefers healthy foods, such as organic foods, vegetarians, consuming nutritious foods and maintaining rest or sleep patterns and participating in physical activities, such as gyms, yoga, cycling and sports are now part of the routines carried out by the younger generation every day. The Impact of Social Media Use in the midst of the globalization era cannot be denied with the presence of social media, it is increasingly needed in everyday life, but social media eliminates the boundaries in socializing, in social media there are no limitations of space and time and with whom they communicate, they can communicate whenever wherever they are and with anyone.